2022
DOI: 10.3390/biom12060832
|View full text |Cite
|
Sign up to set email alerts
|

Non-Equilibrium Protein Folding and Activation by ATP-Driven Chaperones

Abstract: Recent experimental studies suggest that ATP-driven molecular chaperones can stabilize protein substrates in their native structures out of thermal equilibrium. The mechanism of such non-equilibrium protein folding is an open question. Based on available structural and biochemical evidence, I propose here a unifying principle that underlies the conversion of chemical energy from ATP hydrolysis to the conformational free energy associated with protein folding and activation. I demonstrate that non-equilibrium f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 104 publications
(134 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the co-evolution of PfHsp90 and the kinome could have resulted in reduced dependency on a canonical Cdc37 for kinase activation. Indeed, there is evidence that Hsp90 may be able to activate kinases in the absence of Cdc37 [ 121 , 122 ]. Importantly, no study has demonstrated that P. falciparum kinases require PfHsp90 in a mechanism analogous to their yeast and human orthologs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the co-evolution of PfHsp90 and the kinome could have resulted in reduced dependency on a canonical Cdc37 for kinase activation. Indeed, there is evidence that Hsp90 may be able to activate kinases in the absence of Cdc37 [ 121 , 122 ]. Importantly, no study has demonstrated that P. falciparum kinases require PfHsp90 in a mechanism analogous to their yeast and human orthologs.…”
Section: Discussionmentioning
confidence: 99%
“…The ‘Editor’s Choice’ article by Haufeng [ 16 ] discusses whether proteins always fold to a free-energy minimum or whether they can be maintained by energy-consuming processes in functional conformations with elevated free energies. The common view is that chaperones accelerate the kinetics of the folding process so that substrates reach their free-energy minimum.…”
mentioning
confidence: 99%